The Lawn Fertilizer Toolbox - Laurie E. Trenholm; Jason K. Kruse; J. Bryan Unruh (EDIS)
ENH1174, a 3-page fact sheet by Laurie E. Trenholm, Jason K. Kruse, and J. Bryan Unruh, describes the nutrients in fertilizer that are most important for keeping turfgrass healthy and when to fertilize. Published by the UF Department of Environmental Horticulture, October 2010.